Lucid dream induction by auditory stimulation and reality testing during early-morning sleep - Schmidt, Daniel; Erlacher, Daniel (International journal of dream research, 2020)
One challenge in lucid dream research executed in a laboratory setting is the reliable induction of lucid dreams. A possible way to solve this issue is the combination of already known and effective induction techniques (Stumbrys, Erlacher, Schädlich, & Schredl, 2012). The present study combines the wake-up-back-to-bed sleep protocol (WBTB) with reality testing and acoustic stimulation by music. The following question was posed: would repeating the same music presented during the waking dream work session during the subsequent REM sleep increase the chance of a lucid dream experience. In total 21 participants spent a single night in the sleep lab. The whole procedure induced in 3 participants a lucid dream (14.3%), however none of those lucid dreams were verified by LRLR eye signal. The success rate of a combination of auditory stimulation with reality testing thus lies below the success rate of other induction techniques. The incorporation of music as a theme was found in 9 (19.6%) out of 69 dream reports which is in accordance with previously reported incorporation rates. Beside the music presentation, other methodological adjustments were made (e.g., shortening of the first part of the night to 4.5 h), which will be discussed and hopefully help further research to increase lucid dream induction rate.
Gesehen am 07.04.2020